2012
DOI: 10.1212/wnl.0b013e31826e25df
|View full text |Cite
|
Sign up to set email alerts
|

SQSTM1 mutations in frontotemporal lobar degeneration and amyotrophic lateral sclerosis

Abstract: Objective: There is increasing evidence that common genetic risk factors underlie frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). Recently, mutations in the sequestosome 1 (SQSTM1) gene, which encodes p62 protein, have been reported in patients with ALS. P62 is a multifunctional adapter protein mainly involved in selective autophagy, oxidative stress response, and cell signaling pathways. The purpose of our study was to evaluate the frequency of SQSTM1 mutations in a dataset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(187 citation statements)
references
References 42 publications
10
168
2
7
Order By: Relevance
“…In contrast to the findings of Rubino et al 4 we found no significant differences in allelic and genotypic frequencies of the p.(Glu274Asp) or other synonymous variants between our ALS cohorts and controls derived from a UK control cohort and publically available databases. In contrast, the properties of the p.(Pro392Leu) and p.(Glu155Lys) mutations are more likely to contribute pathogenic effects.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the findings of Rubino et al 4 we found no significant differences in allelic and genotypic frequencies of the p.(Glu274Asp) or other synonymous variants between our ALS cohorts and controls derived from a UK control cohort and publically available databases. In contrast, the properties of the p.(Pro392Leu) and p.(Glu155Lys) mutations are more likely to contribute pathogenic effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis of all SQSTM1 variants that are predicted as being pathogenic in published cohorts, [3][4][5][6] and the current study demonstrated that pathogenic SQSTM1 variants are significantly associated with FALS with a combined odds ratio of 3.91 (P MH ¼ 0.0002, Supplementary Table 1). No significant association was found for SALS cases.…”
Section: Identification Of Sqstm1 Sequence Variants In a Uk-fals Cohortsupporting
confidence: 51%
See 2 more Smart Citations
“…This is a multicenter retrospective and exploratory collaborative study in which all the members of the EU EOD consortium [10] and other authors of published studies analyzing the SQSTM1 gene [10,11] were asked to provide available brain MRI scans from the subjects screened in previous studies whether they were FTD/SQSTM1 carriers or not. A subject was considered to be a FTD/SQSTM1 carrier when she/he fulfilled research criteria for FTLD [12] and carried a disease-segregating SQSTM1 genetic variant or, if DNA samples from relatives to demonstrate familial segregation were unavailable, their SQSTM1 variant, was only found in FTLD cases or the variants were more frequent among the cases [9,11].…”
Section: Subject Selection and Comparison Groupsmentioning
confidence: 99%